PENGARUH PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA - Firdaus, Andi Mulawakkan; Wasilatul Murtafiah (Jurnal Penalaran dan Riset Matematika, 2024)
The type of research used in this study is pre-experiment research. This study aims to determine the effect of the application of the Team Games Tournament (TGT) type cooperative model on math learning outcomes. The research design used was One Group Pretest-Posttest Design. This research was conducted at SMP Muhammadiyah Limbung with the total population of all students in grade VIII of SMP Muhammadiyah Limbung in the academic year 2023/2024 spread over 11 classes, namely class VIII-1 to class VIII-11, totaling 385 people. The sample selection technique was simple random sampling, the sample members selected were class VIII.1 SMP Muhammadiyah Limbung with 35 students, consisting of 20 female students and 15 male students. The instruments used in this study were student math learning outcomes tests (Pre Test and Post Test). Data collection techniques in this study were Documentation and Mathematics Learning Outcomes Test, this test was used to measure the level of understanding of mathematics learning outcomes in 8th grade students of SMP Muhammadiyah Limbung. Data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. The results showed that the Team Games Tournament (TGT) type cooperative learning model had an effect on the mathematics learning outcomes of 8th grade students of SMP Muhammadiyah Limbung. This is evidenced by the results of the T-test of 4.35 with a significant level α = 5% and t.table = 2.042. Based on the test criteria, if the t.count ≥ t.table value is obtained, Ha is accepted or 4.35 ≥ 2.048, so H0 is rejected and Ha is accepted. So, the effect of improving student learning outcomes after being given the Team Games Tournament (TGT) type cooperative learning model is 23.3%.